PENGARUH BRAND AMBASSADOR DAN CITRA MEREK TERHADAP KEPERCAYAAN KONSUMEN DAN KEPUTUSAN PEMBELIAN PRODUK GARNIER MEN DI KOTA PEKANBARU - Doni Pratama Tamba; Zulkarnain Zulkarnain; Aida Nursanti (JURNAL ECONOMICA: Media Komunikasi ISEI Riau, 2024)
This research aims to determine the influence of Brand Ambassadors, and brand image on consumer trust and purchasing decisions for Garnier Men products in Pekanbaru City. The population in this study were users of Garnier Men products in Pekanbaru City. The sampling technique used the Cochran formula with a sample size of 150 respondents. The data collection technique uses a questionnaire, this research uses primary data with a path analysis model. The results of this research state that: 1) Brand Ambassadors have a significant influence on Consumer Trust, 2) Brand Image has a significant influence on Consumer Trust, 3) Brand Ambassadors have a significant influence on Purchasing Decisions, 4) Brand Image has a significant influence on Purchasing Decisions, 5) Consumer Trust significant influence on Purchasing Decisions, 6) Brand ambassadors have a significant influence on Purchasing Decisions through Consumer Trust, 7) Brand Image has a significant influence on Purchasing Decisions through Consumer Trust Keyword: Brand Ambassador, Brand Image, Consumer Trust, Purchasing Decisions